Growth of Individual Tomato Fruits under Assimilate Limitation Associated with Successively-later Set Fruits - Rybak, Maria Raquel; Boote, Kenneth J.; Jones, James W. (2017)
The time course of growth of individual tomato fruits (Solanum lycopersicum) was analyzed in relation to the fruit initiation date and cumulative degree days of growth. Experimental data of dry weight (DW), fresh weight (FW), radial diameter (FDIAM), and dry matter concentration (DMC) of three different cohorts of fruits of determinate fresh-market tomato cultivar Florida 47 were determined under field conditions in Florida during spring of 2006 and 2007. Successively later cohorts (1 week intervals) had longer lags prior to rapid growth, slower maximum growth during the rapid phase, and smaller DW, FW, and FDIAM at maturity. These growth patterns were analyzed by fitting the data to a three-parameter Gompertz function for DW, FW, and FDIAM, and to a four-parameter modified Gompertz function for DMC. The good agreement of predicted and measured values indicates that the growth of individual tomato fruits followed the classical S-shaped Gompertz function. The Gompertz function was suitable to describe the slow growth that occurs in tomato fruits immediately after fertilization. The equation was able to predict the increasing duration of this lag and slower maximum growth and smaller final DW, FW, and size for successively later initiated cohorts of fruits. These results confirm the role of sink-source relationships (time of fruit set) on the growth of tomato fruits over time. This study will provide information potentially useful to improve existing tomato crop growth models that are presently limited because they do not predict practical outputs such as fresh weight and size of individual fruits.